wheel walker DESIGN A WHEEL WALKER FOR PEOPLE WITH DISABILITIES LOWER EXTREMITY FUNCTION - Wilutono, Nasrullah; Utami, drg. Naning Kisworo; Prayogi, Bisepta (JURNAL CITRA KEPERAWATAN, 2025)
The main problem that occurs in people with impaired lower extremity function is the risk of falling. For the elderly due to degradation of function or sick conditions, there will be a decrease in the strength of the muscles of the lower limbs or lower extremities can be aggravated by the presence of degenerative diseases such as osteoporosis, Parkinson's, poststroke, and fractures. Lower extremity fractures are mostly the result of accidental trauma, have a high hospitalization rate and require surgery. The impact of falling incidents on the elderly is that they result in various types of injuries, physical and psychological damage. To overcome these problems, it is necessary to design road aids which are improvements to the previous road aids. The wheel walker design method consists of the technical aspects of the mechanical design of the wheel walker, including the components involved, the materials used, and the design principles applied to achieve the optimal performance of the tool. The research design includes tools and materials, research flow diagrams and wheel walker design processes. Based on the results of the research, the wheel walker that has been designed and built in this study meets ergonomic and functional criteria for people with lower extremity function disorders. The design can be adjusted to the needs of the user, providing ease of mobilization and helping to increase the patient's independence in carrying out daily activities. Keywords: Wheel walkr, disabilities, lower extremity